2019
DOI: 10.1111/bcpt.13184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anticholinergic burden on treatment modification, delirium and mortality in newly diagnosed dementia patients starting a cholinesterase inhibitor: A population‐based study

Abstract: Few studies have evaluated the association between anticholinergic burden and treatment modification after starting a cholinesterase inhibitor in clinical practice.We aimed to evaluate the effect of anticholinergic burden on anti-dementia treatment modification, delirium and mortality. We retrospectively analysed older adults (n = 25 825) who started a cholinesterase inhibitor during 2003-2011 from Korean National Health Insurance Service Senior Cohort Database. High anticholinergic burden was defined as an av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 24 publications
1
33
4
Order By: Relevance
“…Despite the fact that robust evidence exists regarding how ACs can affect both cognition and AChEIs per se due to pharmacodynamics interactions, based on their opposing mechanisms of action [17], most were from cross-sectional and short term follow-up study. A recent 36-month follow-up research showed that high anticholinergic burden negatively affected the treatment response to cholinesterase inhibitors and that an average ACB score >3 was an independent prognostic factor for delirium or mortality among dementia patients [18]. However, no clear relationships between ACs and the change of cognition were noted in this study.…”
Section: Introductioncontrasting
confidence: 80%
“…Despite the fact that robust evidence exists regarding how ACs can affect both cognition and AChEIs per se due to pharmacodynamics interactions, based on their opposing mechanisms of action [17], most were from cross-sectional and short term follow-up study. A recent 36-month follow-up research showed that high anticholinergic burden negatively affected the treatment response to cholinesterase inhibitors and that an average ACB score >3 was an independent prognostic factor for delirium or mortality among dementia patients [18]. However, no clear relationships between ACs and the change of cognition were noted in this study.…”
Section: Introductioncontrasting
confidence: 80%
“…Further observational (cohort and case control) studies have described an associated with anticholinergic medication and increased mortality in people without dementia (Cross et al, 2017;Gray et al, 2015) and people with dementia (Gray et al, 2015;Gray & Hanlon, 2016). For instance in a study of 25,825 people with dementia, researchers found that higher anticholinergic burden significantly increased mortality rates (Ah, Suh, Jun, Hwang, & Lee, 2019). Furthermore, anticholinergic burden has been shown to negatively affect the treatment response to cholinesterase inhibitors (Ah et al, 2019;Carnahan, Lund, Perry, & Chrischilles, 2004;Palmer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Increased anticholinergic burden has been associated with increased risk of mortality in older patients [42] . Associations have been identified between anticholinergic medications and increased dementia risk [43] and between anticholinergic burden and mortality in people with dementia [44] . Our results did not identify an association between anticholinergic burden and mortality risk in patients with dementia.…”
Section: Discussionmentioning
confidence: 99%